Borrowing constraints, own labour and homeownership: Does it pay to paint your walls? - Peter Lindner; Thomas Mathä; Giuseppe Pulina; Michael Ziegelmeyer (European Central Bank (ECB), 2020)
Using a dedicated set of questions in the 2014 Luxembourg Household Finance and Consumption Survey (LU-HFCS), we show that a substantial share of households contributes their own labour to the acquisition of their main residence. These contributions help households faced with credit constraints, since they reduce the need for external financing. We develop a simple theoretical model and show that own labour contributions decrease with the level of financial resources available, while they increase with the mortgage interest rate. These theoretical results are supported by empirical analysis, which also shows that own labour contributions vary by household characteristics (age, gender, profession) and by type of dwelling (house, apartment).
Keywords: D14; E43; G21; R21; 330; Borrowing constraints; down payment; own labour; sweat equity; homeownership; household; survey